NILAI DESAIN ACUAN SAMBUNGAN KAYU GESER GANDA DENGAN PAKU BERPELAT SISI BAJA AKIBAT BEBAN UNI-AKSIAL TEKAN MENURUT BERBAGAI ANALISIS PENDEKATAN - Sucahyo Sadiyo; Naresworo Nugroho; Surjono Surjokusumo; Imam Wahyudi (PERENNIAL, 2010)
The purposes of this research are to know the influence of woods specific gravity and nail diameter to reference design value in double shear timber connections with steel side plates nail on four species of Indonesian commercial wood according to various approximation analysis. Analysis is done to four values and it is compared with other research that has been done. This research result from testing which have done by Ziannita (2009) referred as approach of A; result of research of Sadiyo and Sriyanto (2009) and Mansur (2009) referred as approach of B; values referring at literature referred as approach of C and compressive-joint total load divided by nail amount and factor of safety referred as approach of D (Sadiyo and Sriyanto, 2009 and Mansur, 2009). Joint done by using four species of Indonesian commercial wood which is meranti merah (Shorea leprosula), mabang (Shorea pachyphylla), kempas (Koompassia malaccensis) and bangkirai (Shorea laevifolia). Nails that applied in this research are nail with diameter of 4.1 mm length of 10 cm, nail with diameter of 5.2 mm length of 12.5 cm and nail with diameter of 5.5 mm length of 15 cm. The calculation of this research is done according to National Design Specification for Wood Construction-2005. Analysis results indicate that wood specific gravity influence the strength of connection, excelsior wood specific gravity will produce high strength of connection also. This can be influenced by mechanical properties from wood such as maximum crushing strength. Bangkirai have higher specific gravity than three others wood but result approach of D shows that the connections assess reference design value which is lower compared with two other woods (kempas and mabang wood). Then, the bigger on nail diameter brings bigger strength of connection also, but this thing depends on the conditions from nail and quality of nail materials. Key words: compression loading, double shear connections, nail, reference design value, steel side plates.